A REVIEW : ANALYSIS OF BIOACTIVE COMPOUNDS IN ROBUSTA COFFEE LEAVES (Coffea canephora Pierre ex A.Froehner) - Widianingsih, Mastuti (JFM (Jurnal Farmasi Malahayati), 2025)
Robusta coffee leaves (Coffea canephora Pierre ex A. Froehner) contain various bioactive compounds with significant therapeutic potential. The primary compound, chlorogenic acid (CGA), exhibits antioxidant, anti-inflammatory, and metabolic homeostasis-regulating properties, contributing to the management of chronic metabolic diseases such as diabetes, obesity, and cardiovascular disorders. Additionally, CGA demonstrates neuroprotective and anticancer effects. Alkaloids, including caffeine and trigonelline, possess stimulant activity that enhance alertness and physical performance, while flavonoids and xanthones act as potent antioxidants, protecting against cellular damage. Terpenoids are involved in the inhibition of angiogenesis and cancer cell metastasis, alongside exhibiting anti-inflammatory effects. Furthermore, saponins present in Robusta coffee leaves enhance immune responses and help lower blood glucose levels. Overall, the bioactive compounds in robusta coffee leaves present considerable potential for the treatment of metabolic diseases, infections, degenerative disorders, and cancer. However, further research is needed to optimize the extraction methods and practical applications of these compounds in complementary therapeutic products, as well as in the health and cosmetic industries, to fully exploit the therapeutic potential of Robusta coffee leaves.